(untitled) (REVISTA NODO, 2021)
The goal of this work is to analyze the social construction of space in the Puerto Madero neighborhood in Buenos Aires (Argentina) from an ethnographic point of view. To this end, we will analyze representations of space (especially its public space) along with spatial practices. The analysis begins with the urban transformations brought about by the urban renewal project that gave the neighborhood its current configuration. Our results stem from application of Lefebvre’s (1974), the conceptual triad of social construction of space to an ethnographic reconstruction of the daily practices and uses of passers-by in the public spaces of Puerto Madero, as well as the recognition of usual spatial imagery and geographic stereotypes, and the analysis of discursive resources displayed by various actors in the configuration of this urban neighborhood.